State of the art: Semantic-cognitive analysis of journalistic texts - Culqui Martínez, Denice (2022)
This article presents a synthesis of the state of the art of the main cognitive investigations, in relation to journalistic texts focused on metaphorical emissions in the field of national and international soccer. With the purpose of determining and contrasting those already advanced areas with those that are yet to be elucidated, as tools that allow delimiting and identifying key variables in the theoretical perspective of a new line of linguistic research in the Peruvian soccer environment.